Host pathogen interaction, and copper resistance in Xanthomonas associated with citrus canker - Gochez, Alberto Martin (University of Florida, 2020)
Tesis para obtener el grado de Doctor of Philosophy, de la University of Florida (Estados Unidos), en 2014